PENGEMBANGAN MODEL PEMBELAJARAN KIMIA ANALITIK UNTUK MENINGKATKAN MUTU PENDIDIKAN GURU KIMIA - Liliasari, Mrs; Darsati, Mrs Siti (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2002)
The aim of the research is to improve chemistry teacher training program quality, use Analytical Chemistry Teaching Model (MPKA). The improvement should be on student higher order thinking skills. The model is consisting of 23 concepts, which include concepts that name process, concepts that have no perceptible instances, concepts which require knowledge of principles, concepts involving symbolic representation, formula and equation. Those concepts arrange in nine hierarchies on concept map. The model of teaching uses: (a) concept and science process skill approach; (b) problem solving and lecture method, and also laboratory activities; (c) transparency and power point media; (d) essay test. Critical thinking skills developed by the model are elementary clarification, basic support, inference and strategy and tactics. Creative thinking skills developed by the model are: (1) encouraging elegant solution of collision conflict, unsolved mysteries; (2) practicing the creative problem solving process in disciplined systematic manner in dealing with the problem and information at hand; (3) examining fantasies to find solution of real problems; (4) heightening anticipation only enough structure to give clues and direction. The model has been implemented to 82 students in three teacherâs training institutions (LPTK) in Java and Bali. The model improves studentsâ comprehension in Chemistry concepts. It also develops three kinds of logics: group inclusion, proportional and combinatorial. Therefore it is suggested to develop similar models for other courses in perspectives chemistry teachers training program.Key words: Model of teaching, analytical chemistry, critical and creative thinking skills, quality improvement.